Observation of 115 GHz high-order harmonic noise-like pulse in Er/Yb-doped fiber laser. (21st June 2017) - Lin, Qimeng; Hou, Lei; He, Xin; Sun, Jiang; Lu, Baole; Sun, Bo; Chen, Haowei; Bai, Jintao
Abstract: We report on an ultrahigh repetition rate harmonic noise-like Er/Yb-doped double-cladding fiber laser that can operate through the nonlinear polarization evolution mechanism. High-order harmonic noise-like pulses (NLPs) with a repetition rate as high as 115 GHz have been generated in fiber lasers. At the cavity dispersion of net anomalous, the noise-like pulse with the full width at half maximum of 15 nm was generated at a central wavelength of 1560 nm, with an output power of 628 mW at the pump power of 8 W. These results could be useful for understanding the generation of higher power and higher repetition rate NLPs in passively mode-locked fiber lasers.